Penerimaan Masyarakat Kepada Penyandang Disabilitas : (Studi Desa Inklusi Peduli dengan Kelompok Rentan di Kalurahan Sidorejo, Kapanewon Lendah, Kabupaten Kulon Progo) - Sri Murwaningsih; Ratna Sesotya Wedjajati (Sekolah Tinggi Pembangunan Masyarakat Desa APMD, 2021)
Persons with disabilities are included in the marginalized group because of their lack of ability to interact and have difficulty joining community groups. This research looks at the impact of the emergence of